SYNTHESIS AND CHARACTERIZATION OF CHITOSAN MEMBRANES OF CASSAVA PEEL (Manihot esculenta) AND LERI STARCH COMBINATION AS A BIODEGRADABLE PLASTIC: English - Dewi, Pande Putu Indira Prima; Widhiantara, I Gede; Sandhika, I Made Gde Sudyadnyana; Wiradana, Putu Angga; Susilo, Raden Joko Kuncoroningrat (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Problems related to landfills of plastic packaging waste are a source of environmental pollution. This research provides innovation in utilizing biodegradable plastic from cassava and leri peel starch with the addition of chitosan. This study aimed to analyze the results of the synthesis and characterization of chitosan membranes with a combination of cassava and leri peel starch and determine the biodegradation time of biodegradable plastic in EM-4 bioactivation. This study characterized biodegradable plastic membranes using test parameters, namely the SEM, FTIR, Swelling, and tensile strength tests. The biodegradation test was carried out by immersing biodegradable plastic membranes in an EM-4 bioactator for 7 days. Based on the results obtained from the characterization of biodegradable plastic membranes, namely the swelling test with concentrations of 5:3, 7:3, and 9:3, with yield values ​​of 62.9921%, 69.8902%, and 71.4286%. The SEM test obtained the best results at a concentration of 7:3. FTIR test on biodegradable plastic membranes containing hydroxyl (O-H) and carbonyl (C-O) groups. The tensile test obtained optimum results at the concentration of biodegradable plastic membranes, namely 9:3. As for the biodegradation test that has been carried out, the start time for degradation is 3 days.